PENGARUH TRANSFER FISKAL DAN DANA BAGI HASIL TERHADAP PENDAPATAN PER KAPITA KABUPATEN/KOTA DI PROVINSI SUMATERA BARAT - Ariusni Ariusni (Universitas Negeri Padang, 2012)
The general objective of this study was to determine the correct how big the block grant, the specific grant (DAK) and income sharing (DBH) affect per capita income of the people in the districts/cities in West Sumatra Province. While research specially aimed to determine the correct wheter there is a significant influence general allocation fund, spesific grants and income-sharing to income per capita 19 districts/cities in West Sumatra Province. Based on the results of the study indicate that the block grant (DAU) has no effect on income per capita nineteen districts/cities in West Sumatra Province and income sharing (DBH) positive and significant on income per capita of the nineteen ditricts/cities in West Sumatra Province during 2003-2010.